Pengelolaan Pelayanan Pasien Berbasis Web Pada Puskesman Halaban - Isnardi; Rini Asmara; Ikhsan3; Imam Gunawan4 (Prosiding SISFOTEK, 2021)
Information systems have been implemented in various fields, one of which aims to facilitate human activities, the same thing must also be found in health services such as hospitals and health centers. Although in a small scope and sometimes far from the city center, puskesmas have a big role in ensuring the availability of public health services. For this reason, it is necessary for this system to be created and developed at the puskesmas, especially at the Halaban puskesmas. The method used in the design and development of this system uses the waterfall model. The data are taken directly from the Halaban health center and general data can be obtained from various reference reviews that are on the same topic as this research. The results after the trial, this system can run as expected and can be implemented directly at the puskesmas, so that the service process is much easier. It's just that the system still needs to be developed so that it can be integrated again with other systems.